A complete right oculomotor nerve palsy secondary to carotid cavernous fistula with a background of poorly controlled diabetes: a case report - Ismail, Hazwani; Wei, Chao Loh; Mohd Yaakob, Mohd Naim (Sapporo Ika Daigaku, 2022)
Background: The coulometer or the third cranial nerve gives innervation to the four of the six extraocular muscles, namely the medial rectus, superior rectus, inferior rectus, inferior oblique. This cranial nerve is responsible for the upward and downward as well as adduction movement of the eyeball. It also retract the upper eyelid by innervating the levator palpebrae superioris muscle.Oculomotor nerve regulates the pupillary constriction via the parasympathetic nervous system. Oculomotor nerve palsy may affect any of these roles depending from its aetiology. Case presentation: We are reporting a case of complete right sided oculomotor nerve palsy secondary to carotid cavernous fistulain a poorly controlled diabetic patient. This patient had a complete right sided ptosis with the eyeball deviated to the ‘down and out’ position in keeping with dilated pupil. A magnetic resonance angiography had confirmed the diagnosis of carotidcavernous fistula of which an urgent embolization procedure was performed. Conclusions: Diagnosing an oculomotor cranial nerve palsy correctly and to determine its exact etiology is vital. A complete, pupil-involving oculomotor nerve palsy warrants an urgent radiological imaging as to accurately localized the lesion that give rise to the presenting symptoms.